SISTEM AKUNTANSI PENJUALAN KREDIT PADA PT SETAJAYA TOYOTA, DEPOK - Enggun Gunawan; Syalazkiya Tamara Fitriani; Istna Fibriyadi (JURNAL LENTERA AKUNTANSI, 2024)
Credit Sales Accounting System at PT. Setiajaya Toyota Depok. The purpose of this research is to find out how the accounting system, accounting recording system, internal control system, and documents are used in credit sales activities at PT. Setiajaya Toyota Depok. Field studies and literature studies were used to conduct research. To collect data, observation and interview methods were used. The steps used include discussing the sales accounting system, credit sales system accounting records, documents used, and internal control of the credit sales system at PT. Setiajaya Toyota Depok.